THE MAIN CHARACTER INNER CONFLICT ELEMENT IN DRAMA MANUSCRIPT NYANYIAN ANGSA CREATION BY ANTON CHEKOV AND THE IMPLICATIONS TOWARD LITERATURE TEACHING - Yogi Purnama; Kartono Kartono; Sohibul Anwar (Universitas Indraprasta PGRI, 2020)
Abstract: The inner conflict element which happen to main character in the drama script nyanyian angsa creation by Anton Chekov. The research method which using for analysis the script is qualitative method that description analysis. Research focus internal conflict element in drama script nyanyian angsa creation by Anton Chekov with subject focus element Id >< Ego, Id >< Eros and Superego >< Thanatos. The research instruments analyze scene that have an element of inner conflict in the script nyanyian angsa creation by Anton Chekov. To get the results the writer using presentation table from the element of inner conflict that accumulated. The impact of implications for students, the students must be directly involved actively in literary learning activities that is drama script in the school. The student also required to understand the contents of the drama script very well. To improve literature learning that is drama script, students must improve own learning method outside of school hours, for example be part of theatre extracurricular activities. This is intended so that the ability of students can be channel properly. Key words: inner conflict, drama script, literature teaching.